Primary Malignant Melanoma of the Genitourinary Tract with Upper and Lower Tracts Involvement. (28th August 2013) - Sutton, Broderick; Chan, Robert; Sutton, Mark; Boone, Timothy
Abstract : A 91-year-old female presented with lower extremity swelling and shortness of breath. Laboratory analysis revealed elevations in blood urea nitrogen and creatinine along with microscopic hematuria on urinalysis. Computed tomography imaging showed moderate right hydronephrosis with dilatation of the proximal ureter with a soft tissue density at a transition point. Endoscopic evaluation revealed multiple raised, fleshy, and hemorrhagic masses throughout the bladder which are present in both ureters. Biopsy of these lesions revealed malignant melanoma invading the lamina propria. No dermatologic lesions were identified suggesting a primary malignant melanoma of the genitourinary system.